Roles of estrogens, estrogen-like compounds, and endocrine disruptors in adipocytes - Lizcano, Fernando (Frontiers in Endocrinology, 2022)
Sex hormones strongly influence the distribution of body fat and the differentiation of adipocytes. Both estrogens and testosterone affect the physiology of adipocytes, but in different ways, with changes ranging from the control of hunger and satiety at the level of the central nervous system to the energy produced by adipose cells. Central obesity, characterized by a greater accumulation of adiposity in the abdominal region, has been associated with an increased risk of mortality. One of the determinants of body fat distribution is sex hormones. Both estrogens and androgens seem to influence the distribution of body fat directly and indirectly. Estrogens have a beneficial effect on vasomotor symptoms typical of menopause. Moreover, estrogens and estrogen receptors regulate various aspects of glucose and lipid metabolism. Even though several studies have debated that the absence of estrogens is a key factor in the appearance of cardiovascular disease during the menopausal period. The influence of the absence of these hormones and their relationship with obesity in women during menopause are not clear. This systematic review discusses the role of estrogens and estrogen receptors in the differentiation of adipocytes and their control by the central nervous system. Emphasis is placed on estrogen-like compounds and the role of endocrine disruptors with estrogenic effects on the physiology of adipose cells. Finally, the interaction between decreased estrogen secretion and the prevalence of obesity in menopausal women is examined. We will consider whether the absence of estrogens has a significant effect on obesity in menopausal women.